INTELLIGENCE PROPERTIES AND EMOTIONAL INTELLIGENCE IN THE STRUCTURE OF PERSONALITY AS FACTORSOF PERSONAL/ PROFESSIONAL ACHIEVEMENT - Marta Matulcikova; Daniela Brevenikova (European Scientific Journal, ESJ, 2014)
The paper presents partial results of an interdisciplinary research project into business – academia relationships, named “Methods and Principles Applied in the Preparation of Structure and Content of Sobject Disciplines Promoting the Development of Knowledge of Economics and Business Skills of Students Pursuing Non-economics Study Programmes of the Level II of Higher Education (KEGA 006EU-4/2013) carried out at the University of Economics in Bratislava”. The present paper deals with the role of emotional intelligence and intelligence properties in the structure of personality as a significant factor of success at work. These two components are described and analysed from the aspect of employer entities and that of educational institutions. Theoretical part of the paper draws on research in economics, management education, and psychology in English-speaking countries as well as in Slovakia and the Czech lands. While respondents of the questionnaire survey who represent business/employer entities give their opinions of what kind of personality properties they expect from successful job applicants, respondents from educational institutions express their ideas of the kind of properties that should be developed in their students to make them employable after completing their studies. The aim of the paper is to suggest – on the basis of analysis respondents’s answers – to educational institutions in Slovakia ways of striking a balance between developing their learners’ intelligence properties and developing their emotional intelligence so that their future graduates have a good chance to succeed on the labour market.